2017
DOI: 10.1021/acs.jced.7b00241
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor–Liquid Equilibrium for the Binary and Ternary System with Isobutyl Alcohol, Isobutyl Acetate and Dimethyl Sulfoxide at 101.3 kPa

Abstract: The isobaric vapor−liquid equilibrium (VLE) data for the binary systems isobutyl alcohol + dimethyl sulfoxide (DMSO), isobutyl acetate + DMSO, and ternary system isobutyl alcohol + isobutyl acetate + DMSO were measured at 101.3 kPa. All of the binary VLE data passed Wisniak's modifed Herington area test and Wisniak point and area test. Ternary VLE data passed Wisniak point test. The VLE data of binary systems were correlated with NRTL, UNIQUAC, and Wilson models. The ternary VLE behavior were successfully pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The models are taken from Aspen Plus V8.0 and are presented in Table . The interaction parameters of these models were regressed by minimizing the following OF: where σ x and σ y are standard deviations of the liquid and vapor concentrations, respectively (σ T = 0.1 K, σ p = 0.075 kPa, σ x = 0.005, and σ y = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…The models are taken from Aspen Plus V8.0 and are presented in Table . The interaction parameters of these models were regressed by minimizing the following OF: where σ x and σ y are standard deviations of the liquid and vapor concentrations, respectively (σ T = 0.1 K, σ p = 0.075 kPa, σ x = 0.005, and σ y = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…The ternary system was found to be thermodynamically consistent by the Wisniak L-W test. , The test is described by the following equations. According to this method, the average and maximum values of F k are 1.212 and 3.692, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental data of tert -butanol­(1) + chlorobenzene(3) and tert -butyl acetate(2) + chlorobenzene(3) systems were correlated with the Wilson, NRTL, and UNIQUAC activity coefficient models. The interaction parameters of these models were adopted by minimizing the objective function (OF): N is the number of experimental points; T i exp and T i cal are the experimental and calculated temperatures, respectively; and y k , i exp and y k , i cal are the experimental and calculated vapor mole fractions, respectively. The correlated parameters of the above-mentioned three models, the root-mean-square deviations (rmsd) of the vapor mole fraction, and the boiling temperature between the experimental and calculated data are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is common to employ methods involving the addition of mass separation agents and utilize separation techniques such as extraction and extractive distillation. Liu et al investigated the possibility of separating the azeotropic mixture of IBA and IBAC using dimethyl sulfoxide. The isobaric vapor–liquid equilibrium (VLE) data of the system were determined at atmospheric pressure, and the results demonstrated that the addition of dimethyl sulfoxide significantly enhanced the relative volatility of IBAC to IBA …”
Section: Introductionmentioning
confidence: 99%